Psychological Factors Influencing Academic Achievement among Secondary School Students in Shamva District of Mashonaland Central Province in Zimbabwe: A Recent Study - Kasowe, Rittah (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
The study looked into the psychological factors that influence secondary school adolescents' academic achievement in the Shamva district. The design for the study is ex-post-facto. The current study population consists of 300 participants who were chosen at random and independently. To collect data, two standardised instruments labelled "Psychological Factors Assessment Questionnaire and Economics Achievement Test" were used. The instruments' reliability was 0.91 and 0.86, respectively. For the investigation, two hypotheses were formulated. An independent t-test was used to analyse the data collected. The results of the data analysis revealed that school phobia has a considerable impact on children' academic progress, whereas achievement motivation had no effect. The researchers recommended that teachers, parents, counsellors, and school officials be made aware of the existing association between self-concept, anxiety, achievement motivation, and focus of control and academic achievement based on the findings of this study. This would allow them to provide better, more useful, and relevant educational, vocational, personal, and social services to secondary school students, teachers, parents, school officials, and the community, allowing them to recognise and appreciate the presence of individual differences among students and how to best reinforce them in all situations.